An integrated production, inventory and transportation decision in a whole green manufacturing supply chain. (2017) - ,; Zhang, David Z.
This paper proposes model to integrate production, inventory and transportation decision in a whole green manufacturing supply chain. The integration includes reuse and remanufacturing of returned used products. The manufacturing supply chain consists of tier-2 and tier-1 suppliers, a manufacturer, distributors, retailers and a third party. The manufacturer dissembles used products into parts. Reusable parts are remanufactured and reused again in finished products. A mathematical model is developed to coordinate production, inventory and transportation decision which considers multiple products simultaneously with determination of number of transportation units needed to deliver the finished products subject to their own capacities. Solution methods for the model are proposed based on three types of coordination mechanisms, decentralised, semi-centralised and centralised decision processes. The model and solution methods are illustrated with two numerical examples and results and findings are discussed.